Creep behavior and postcreep thermoelectric performance of the n-type half-Heusler alloy Hf0.3Zr0.7NiSn0.98Sb0.02. (June 2019) - Al Malki, M.M.; Qiu, Q.; Zhu, T.; Snyder, G.J.; Dunand, D.C.
Abstract: When subjected to uniaxial compressive stresses at 600°C, the n-type ZrNiSn-based half-Heusler alloy Hf0.3 Zr0.7 NiSn0.98 Sb0.02 exhibits Newtonian flow, consistent with diffusional creep of its fine-grain (1–7 μm) microstructure achieved via spark-plasma sintering of powders. In addition to its promising thermoelectric performance at high temperatures, this alloy can sustain very high compressive stresses at 600°C (from 21 to 359 MPa, for ~ 23 days) without macroscopic failure. However, the brittle nature of the alloy leads to the formation of numerous cracks at such high stresses, which in turn deteriorate the thermoelectric performance. Among thermoelectric materials mechanically tested at high temperature to date, the present ZrNiSn-based half-Heusler alloy has the highest creep resistance. Given their high melting temperature, stiffness, and creep resistance, half-Heusler alloys appear very well suited for long-term thermoelectric applications where high stresses and temperatures are present. Graphical abstract: Image 1 Highlights: Hf0.3 Zr0.7 NiSn0.98 Sb0.02 creep via diffusion-based mechanism at 600, half its absolute melting point. Hf0.3 Zr0.7 NiSn0.98 Sb0.02 is the most creep-resistant thermoelectric material measured to date. Cracks formed at high stresses during creep deteriorate thermoelectric performance.